Genetic polymorphisms of HbE/beta thalassemia related to clinical presentation: implications for clinical diversity - Azman, Nurul Fatihah; Abdullah, Wan Zaidah; Hanafi, Sarifah; Diana, R.; Bahar, Rosnah; Johan, Muhammad Farid; Zilfalil, Bin Alwi; Hassan, Rosline (Annals of hematology, 2020)
HbE/Beta thalassemia (HbE/β-thalassemia) is one of the common genetic disorders in South East Asia. It is heterogeneous in its clinical presentation and molecular defects. There are genetic modifiers which have been reported to influence the disease severity of this disorder. The aim of this study was to determine the genetic polymorphisms which were responsible for the disease clinical diversity. A case-control study was conducted among Malay transfusion-dependent HbE/β-thalassemia patients. Patients who were confirmed HbE/β-thalassemia were recruited and genotyping study was performed on these subjects. Ninety-eight patients were selected and divided into moderate and severe groups based on clinical parameters using Sripichai scoring system (based on hemoglobin level, spleen size, growth development, the age of first transfusion and age of disease presentation). Forty-three (44.9%) and 55 (56.1%) patients were found to have moderate and severe clinical presentation, respectively. Genotyping analysis was performed using Affymetrix 6.0 microarray platform. The SNPs were filtered using PLINK and Manhattan plot by R software. From the GWAS results, 20 most significant SNPs were selected based on disease severity when compared between moderate and severe groups. The significant SNPs found in this study were mostly related to thalassemia complications such as rs7372408, associated with KCNMB2-AS1 and SNPs associated with disease severity. These findings could be used as genetic predictors in managing patients with HbE/β-thalassemia and served as platform for future study.